'It's because I like things... it's a status and he buys me airtime': exploring the role of transactional sex in young women's consumption patterns in rural South Africa (secondary findings from HPTN 068) - Meghna Ranganathan; Lori Heise; Catherine MacPhail; Heidi Stöckl; Richard J. Silverwood; Kathleen Kahn; Amanda Selin; F. Xavier Gómez-Olivé; Charlotte Watts; Audrey Pettifor (BMC, 2018)
Abstract Background 'Transactional sex', defined as a non-marital, non-commercial sexual relationship in which money or material goods are exchanged for sex, is associated with young women's increased vulnerability to HIV infection. Existing research illustrates that the motivations for transactional sex are complex. The fulfilment of psycho-social needs such as the need to belong to a peer group are important factors underlying young women's desires to obtain certain consumption items and thus engage in transactional sex. Methods We use a mixed-methods approach to explore the relationship between transactional sex and consumption patterns among young women in rural Mpumalanga province, South Africa. In the secondary analysis of 693 sexually active young women, we use factor analysis to group the different consumption items and we use multivariable logistic regression to demonstrate the relationship between transactional sex and consumption patterns. The qualitative study uses five focus group discussions and 19 in-depth interviews to explore further young women's motivations for acquiring different consumption items. Results The quantitative results show that young women that engage in transactional sex have higher odds of consuming items for entertainment (e.g., movie tickets) than on practical items (e.g., food and groceries). The qualitative findings also revealed that young women's perceptions of items that were considered a 'need' were strongly influenced by peer pressure and a desire for improved status. Further, there was a perception that emerged from the qualitative data that relationships with sugar daddies offered a way to acquire consumer goods associated with a 'modern lifestyle', such as items for personal enhancement and entertainment. However, young women seem aware of the risks associated with such relationships. More importantly, they also develop relationship with partners of similar age, albeit with the continued expectation of material exchange, despite engaging in the relationship for love. Conclusion This study shows that young women are willing to take certain risks in order to have a degree of financial independence. Interventions that provide alternative methods of attaining this independence, such as the provision of cash transfers may have potential in preventing them from engaging in transactional relationships. Further, the psycho-social reasons that drive young women's motivations for consumption items resulting in risky sexual behaviours need to be better understood.